Explaining the Structural Model of Social Anxiety Based on Early Maladaptive Schemas and Family Performance - Naderzadeh, Himan; Salehi, Mahdieh; Ja’fari Roshan, Marjan; Kochak Entezar, Roya (Novelty in Biomedicine, 2020)
Background: The purpose of study was to determine the mediation role of early maladaptive schemas in the relationship between family performance and social anxiety features of students. Materials and Methods: This study utilized a descriptive correlational design and statistical population of this study was included of all students of Marivan city, with the quantity of 4134 in 2016-2017, through them by an available sampling, 400 students were selected. Research tools were family assessment device by Epstein et al (1983), schema questionnaire- short form by Young (1990), social anxiety by Connor et al (2000). Results: Results showed that early maladaptive schemas mediate the relationship between family performances and social anxiety features (β=0.52, p=0.001). Conclusion: Since parental behaviors is one of the most important affecting factors on early maladaptive schemas and formulation of social anxiety features subsequently; Therefore it is necessary for the prevention and treatment of social anxiety disorder pay special attention to the parent’s behaviors and early maladaptive schemas.